NASKAH FILM TELEVISI GENRE ROMANCE COMEDY “PEMUDA IDAMAN #NGACA” - Rogo Wibowo Bima Aji; Ilham Moch. (Publika Budaya, 2017)
AbstractThis television movie script "Pemuda Idaman #ngaca" romance comedy genre discusses about a set of problems faced by single man (single) in finding his ideal partner. The purpose of producing this work is to provide the moral message about the meaning of the mirroring (preparing ourselves) through television screenwriting "Pemuda Idaman #ngaca." This work describes the story of a single man looking for a woman of his dreams which packaged in a comedy. The reconstruction of the characters in this script uses physical constitution of the psychological theory of Ernst Kretschmern to describe the physical form of the characters in the script. The creator collecting data and facts (news) observation in making this work on the phenomenon of singles in Indonesia and based on personal experienced of the creator in the composing idea, so expected with the moral messages preparing ourselves can be delivered through the television movie script "Pemuda Idaman #ngaca." The result of this work is the screenplay television movie of romance comedy as the genre in the title "Pemuda Idaman #ngaca."